2017
DOI: 10.17294/2330-0698.1414
|View full text |Cite
|
Sign up to set email alerts
|

Models for Predicting Incident Delirium in Hospitalized Older Adults: A Systematic Review

Abstract: Centered Research and Reviews (JPCRR) is a peer-reviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This is important, because machine-learning approaches have emerged and evolved during these recent years. Other systematic reviews have exclusively studied older adults ( 23 , 24 ), excluded validation studies ( 25 ), or were restricted to cardiac surgery patients ( 22 ). The studies included in our review were summarized in detail in terms of candidate predictors, final model predictors, and risk of bias ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because machine-learning approaches have emerged and evolved during these recent years. Other systematic reviews have exclusively studied older adults ( 23 , 24 ), excluded validation studies ( 25 ), or were restricted to cardiac surgery patients ( 22 ). The studies included in our review were summarized in detail in terms of candidate predictors, final model predictors, and risk of bias ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of four systematic reviews were identified that reported on CPMs for postoperative delirium in elderly non-ICU patients 9 21–23. Altogether, the systematic reviews covered a time period from 1 January 1990 to 1 January 2017 with partial overlap.…”
Section: Resultsmentioning
confidence: 99%
“…For patients under mechanical ventilation admitted in the ICU the percentage of delirium exceeds 75% ( Ely et al, 2004 ). Older age, decreased functional status, cognitive impairment (even mild), depression and comorbidities constitute the most common predisposing factors for delirium, while a subjacent infection, acute or severe illness, pain, anemia, anesthesia and drugs (including sedative hypnotics and anticholinergics) are the most frequently encountered precipitating factors ( Kalimisetty, Askar, Fay, & Khan, 2017 ; Marcantonio, 2017 ; Wakefield, 2002 ). Undernourishment and dehydration on admission might be aggravating factors ( Wakefield, 2002 ).…”
Section: Usual Complications In Hospitalized Pwp and Covid-19mentioning
confidence: 99%